Harmonised life-cycle global warming impact of renewable hydrogen - Valente, Antonio; Iribarren, Diego; Dufour, Javier (Journal of cleaner production, 2017)
An increasing number of studies addressing the Life Cycle Assessment (LCA) of hydrogen energy systems is found in the scientific literature. Most of these studies are comparative and show significant differences in terms of methodological choices. These differences significantly affect the results of the LCA studies and hamper their robust interpretation, especially when comparing results from different studies. Hence, harmonisation of the results under a consistent methodological framework is needed. This article defines a protocol for the harmonisation of the life-cycle global warming impact of hydrogen. Furthermore, the protocol is applied to renewable hydrogen based on a thorough literature survey of relevant LCA case studies classified by hydrogen-production technological category: thermochemical, electrochemical, and biological. In this sense, the two main outcomes of the study are the harmonisation protocol and the initial library of harmonised carbon footprints of renewable hydrogen for 71 case studies. Key methodological choices subject to harmonisation include (i) attributional approach, (ii) functional unit, (iii) system boundaries, and (iv) multifunctionality approach. Harmonisation is found to affect more significantly the thermochemical and biological categories than the electrochemical one. Nevertheless, risk of misinterpretation is found and exemplified in every technological category. The sources of potential misinterpretation are found to be usually linked to inconsistencies in terms of system boundaries (e.g., hydrogen compression) and, when applicable, multifunctionality approaches. Future LCA practitioners are highly recommended to use the proposed protocol to provide, along with their own results, the harmonised global warming impact of hydrogen in order to enhance current and future result interpretation when comparisons are made. [Display omitted] •Formulation of a robust harmonisation protocol for the carbon footprint of hydrogen.•Application of the protocol to conventional H2 and 139 case studies of renewable H2.•Calculation of the harmonised carbon footprint of 71 case studies of renewable H2.•Harmonisation is found to prevent misinterpretation in comparative studies.•Higher influence on thermochemical and biological H2 than on electrochemical H2.